Training for jobs of the future: Improving access, certifying skills, and expanding apprenticeship - Robert Irving Lerman; Pamela J. Loprest; Daniel Kuehn (Institute of Labor Economics (IZA), 2020)
Long run labor market trends in the American economy pose significant challenges. The employment-to-population ratio has steadily fallen. Growth in real money wages has been slow, with the most rapid gains taking place among workers at the top of the earnings distribution. One source of these trends is low starting wages, which suggests weak transitions from school to the labor market. Limited skills relative to the demands of employers also play a role. This paper proposes three major policy initiatives for upgrading and expanding worker training to bolster productivity and wages: 1) Improve access to in-demand training through better information, technology, and targeted funding; 2) Strengthen connections between career and technical education and training and employer needs through competency-based training, career pathways, and improved certification and verification of skills. 3) Build a robust apprenticeship system that emphasizes learning by doing in a context that involves apprentice contributions to production and culminates in a respected occupational credential. The strategies go beyond the "academic-only" approach commonly pursued in the US. They widen routes for young workers to rewarding careers, and help experienced workers adapt to changing labor markets with improved options over the life course for learning and documenting skills. By upgrading information and using approaches that recognize differences in learning styles, we believe the proposed policies will build, sustain, and recognize a diverse set of skills that will make the majority of American workers more productive and more resilient, strengthen the economy, the budget, and substantially raise living standards for tens of millions of Americans.
Keywords: J08; J24; M53; 330; apprenticeship; training; skills; job matching; certification